Sterilizing Capital inflows. (Economic Issues; Economic Issues ;, 1997)
Developing countries fortunate enough to experience capital inflows haveseen rising levels of investment and enhanced economic growth. Capitalinflows have a negative side, however, in that they tend to appreciatethe domestic currency, making exports less competitive, and to encourageinflation. One defense against these destabilizing effects is to sterilize capital inflows by reducing the domestic component of themonetary base through the various initiatives explained in thispamphlet.